Potensi Vegetasi Non Kayu yang dimanfaatkan oleh Masyarakat di Distrik Unurum Guay, Kabupaten Jayapura - Lani Kawengian; Basa Rumahorbo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2009)
The study on the potensial of Non Timber Forest Product (NTFP) used by people in District Unurum Guay, Jayapura was done in January to April 2007 using survey methods. The result showed that there were 85 species of plant consisted of 32 families. Some of them, used as food source (28,23%), medicinal plants (29,41%), furniture and buiding material (22,35%), as tools for ritual ceremony and traditional belief (17,65%), ornamental plant (16,47%) and traditional weapon and other (20%). The processy of the plant were varies, depended on their utilities, for example as food source, it can boiled, fried, grilled, cooked traditional or freshly eaten. Key words: NTFP, Unurum Guay, Jayapura.